CREATING COMPETITIVE ADVANTAGE IN MANAGEMENT STRATEGIES FOR RICE MILLS - Pratama, Febby Candra; Salim, Ubud; Indrawati, Nur Khusniyah (Universitas Brawijaya, Indonesia, 2019)
This study aims to explain the ability to operate rice mills in the long run. This is a qualitative study with a case study design conducted at the Djasa Bhakti rice mill in Turen, Malang. The results of this study indicate that the rice mill environment consists of external and internal. External companies consist of consumers, competitors, suppliers, and government policies. Observation of the external environment is done to find out opportunities, especially for observations of competitors and government policies carried out through the PERPADI Business Community. The internal company itself consists of production capabilities, human resources, marketing, and finance. The internal company continues to be improved to get opportunities. Cost leadership strategies are applied to companies that make companies that can sell 50 tons per month and have competitive advantages. Based on its assets and turnover, PP Djasa Bhakti is a medium-scale rice mill SME. Therefore, future researchers can conduct research related to strategy management practices and competitive advantage in both micro and small scale rice mills and other SMEs.